The Postal Sector Between General Interest and Economic Efficiency A theoretical approach - GASMI, Chaker (Finance and Business Economies Review, 2019)
In this article we will try to highlighting the problematic of introducing concurrence in the postal sector in order to increase both of his economic efficiency and his social efficacy; this filed was and still one of the most public sector which politicians and economists tried to reform it; but without the appropriate theoretical concepts there tries were unsuccessfully. We will do demonstrate that this sector can be open to the concurrence and there is no problem to procure the postal public service under the appropriate organizational structure after the liberalization of this one.